On the molluscan fauna of Lakshadweep included in various schedules of Wildlife (Protection) Act of India - A. Bijukumar; R. Ravinesh; A. R. Arathi; K. K. Idreesbabu (Journal of Threatened Taxa, 2015)
Out of the 24 species of marine molluscs included in Schedule I and IV of the Wildlife (Protection) Act (WPA) of India, 19 species were recorded from the coastal waters of Lakshadweep.  A recent survey conducted by the authors recorded the presence of 14 scheduled molluscs in Lakshadweep.  Scheduled species such as Placuna placenta (recorded from Kavaratti) and Tudicla spirillus (recorded from Kalpeni) are new records from Lakshadweep.  The paper provides details for taxonomic identification of scheduled molluscs and discusses strategies for conservation of scheduled molluscs of Lakshadweep.